A Debreceni Egyetem Sebészeti Műtéttani Tanszékének története (1951–2017) - Mikó, Irén; Furka, István (Gerundium, 2018)
History of the Department of Operative Techniques and Surgial Research, Faculty of Medicine of the University of Debrecen. The Authors describe the establishment of the four Institutes of Surgical Anatomy and Operative Techniques in the 1951/1952 academic year in the Hungarian Medical Faculties. Then they introduce the 3 eras of the Institute in Debrecen: I. 1951-1986. (directed by Dénes Nagy from 1951 till 1953 and György Bornemisza from 1953 till 1986), II. 1986-2000 (directed by István Furka), III. 2000-2013 (directed by Irén Mikó). During that time the Institute had different names: 1. 1951-1972: Institute of Surgical Anatomy and Operative Techniques, 2. 1972-2000: Institute of Experimental Surgery, 3. 2000-2004: Institute of Operative Techniques and Surgical Research, 4. 2004- Department of Operative Techniques and Surgical Research. The Authors review the wide spectrum of the educational and research work during the past (almost) 60 years. The Reader can have insight into the development of the Department, the accession of territory, the work of the Microsurgical- and Laparoscopic Educational and Training Centers and can get acquinted with the museums of the Department established by Prof. István Furka and Prof. Iren Mikó: Museum of Surgical Suture Materials, Exhibition of Surgical Staplers’ History, Sun Lee Microsurgical Museum, Memorial Place for Janos Veres (inventor of the Veres-needle that is used for laparoscopic interventions worldwide).